Chromatic City. Applying s-RGB Design to contemporary space - Antonio Acierno (TRIA Urban Studies, 2019)
The ecological approach to urbanism recently became a main interest in the international disciplinary debate, in response to new social demands: climate change, reduction of natural resources, regeneration of urban abandoned land, perception of unsafety in public space call for changing approach to territory development. The book focuses on the "multi-scalar design", a practice able to act on open spaces, ecological networks and green infrastructures but also on regeneration of the urban organism's neuralgic parts. The book supports a proposal that integrates the territorial vision offered by the green-blue infrastructures with the regeneration of disused and abandoned urban spaces applying recent tools such as urban acupuncture or tactical urbanism, the latter ones revisited according to a design and participatory perspective. Moreover, the perception of unsafety of public spaces is rising as a focal problem for urban policies. Therefore, the methodological design proposal is completed giving specific attention to recent guidelines for urban safety design. The idea of joining these approaches at different levels, from territorial to micro-urban ones, is defined the "s-RGB Design" (safe Regeneration and Green Blue Design).